Optimization design of spinning process of titanium alloy cylinder based on numerical simulation technology. (March 2020) - Guan, R Y; Xu, H Q; Tao, H; Guo, Y M; Lu, B; Zheng, H W
Abstract: Power spinning is a very complicated plastic forming process, and its processing quality involves many and complicated process parameters. The simufact.forming software is used to simulate the power spinning of the titanium alloy cylindrical parts. The effects of technological parameters such as attacking angle, roller nose radius, feed rate, spinning temperature, etc. on cylindrical parts accuracy, spinning force, and stress-strain distribution are systematically studied. The causes of spinning process defects are analyzed, and the sensitivity of process parameters that affected spinning quality is ranked. Through orthogonal test analysis, it is determined that a set of optimal process parameters for the titanium alloy cylindrical part spinning process: attacking angle is attacking angle 20°, the roller nose radius is 10mm, feed rate is 1mm/r, spinning temperature is 850°C. The spinning process of titanium alloy cylindrical parts is initially formed, which lays the foundation for the subsequent spinning process tests of titanium alloy cylindrical parts.